1999
DOI: 10.1088/0954-3899/25/9/302
|View full text |Cite
|
Sign up to set email alerts
|

Pair creation of neutral particles in a vacuum by external electromagnetic fields in 2 + 1 dimensions

Abstract: Neutral fermions of spin 1 2 with magnetic moment can interact with electromagnetic fields through nonminimal coupling. In 2+1 dimensions the electromagnetic field strength plays the same role to the magnetic moment as the vector potential to the electric charge. This duality enables one to obtain physical results for neutral particles from known ones for charged particles. We give the probability of neutral particle-antiparticle pair creation in the vacuum by non-uniform electromagnetic fields produced by con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 15 publications
2
24
1
Order By: Relevance
“…Again retaining only leading terms in the limit L 1 , L 2 → ∞ (neglecting in particular oscillating terms) and taking into account Eqs. (16) and (21), we find…”
Section: Creation Of Neutral Fermionsmentioning
confidence: 57%
See 1 more Smart Citation
“…Again retaining only leading terms in the limit L 1 , L 2 → ∞ (neglecting in particular oscillating terms) and taking into account Eqs. (16) and (21), we find…”
Section: Creation Of Neutral Fermionsmentioning
confidence: 57%
“…The results of Ref. [16] seem to be reasonable, but essentially use specific gamma matrices in 2 + 1 dimensions, and cannot provide a complete description of the effect.…”
Section: Introductionmentioning
confidence: 91%
“…Forms of electric field configurations permitting exact solutions, and QES states based on sl (2) It has been shown that the two-dimensional Dirac-Pauli equation is equivalent to a twodimensional Dirac equation minimally coupled to a vector potential by a duality transformation [14,25]. However, as mentioned in Sect.I, the square of the Dirac Hamiltonian minimally coupled to a vector potential is proportional to the Pauli equation up to an additive constant.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the situation for the AC effect is equivalent to a (2+1)-dimensional problem because of the specific field configuration. Recently, we have calculated the probability of neutral particle-antiparticle pair creation in the vacuum by external electromagnetic fields in 2+1 dimensions, based on the nonminimal coupling [14]. Both scattering and bound-state problems in external fields are easier in 2+1 dimensions.…”
Section: Summary and Discussionmentioning
confidence: 99%